The rural landscape of Southern Sicily in the 5th century AD: the case of Cignana - (:unkn) unknown (My University, 2023)
The fifth century was a period of profound changes in the Sicilian countryside. Transformations took place almost everywhere, along the coastline and further inland. Some sites were destroyed and abandoned after the middle of the century; others survived and expanded considerably. It is the case of the villa at Cignana, near Agrigento, which represents our study case. On the ruins of a luxurious dwelling, abandoned after the middle of the third century CE, simple rectangular structures differently orientated arose. In 2006, archaeological excavations showed that these buildings covered a much larger area than the previous one. Most pottery dates to the fifth century and comes from Vandal Africa, highlighting narrow ties with north-eastern Tunisia. Cignana is not an isolated case. The field surveys in the surroundings of the villa pinpointed at least three other significant sites, yielding the same ceramic assemblages and a strong predominance of African imports. The data we gathered prompts us to reflect on the socio-economic or political reasons that fostered the development of sizeable rural settlements. A process particularly involving the southern Sicily countryside
Keywords: African Research